Together against doping: doping prevention from nada Germany - Müser, D. (Journal of Science and Cycling, 2017)
TOGETHER AGAINST DOPING is a national program run by the Prevention Department of the National Anti Doping Agency Germany (NADA). TOGETHER AGAINST DOPING offers athletes and those who work with them a personal platform and concrete support in their efforts toward clean sport. Awareness for clean sport needs to be raised among young athletes in particular, who need guidance in everyday situations. In addition to the athletes and those close to them (coaches, doctors, assistants, parents, teachers), the German federal and state governments, as well as individual districts and many sport organizations, come together to form the foundation of TOGETHER AGAINST DOPING.